Creative sustainability: gamifying the creative process and creating new possibilities for forgotten materials - Souza , Rosiane de Oliveira; Yecker, Bruna Duque; Rodrigues, Ana Carolina Caldas; Costa, Naiara Vilela (National Journal of City Management, 2023)
Through the present paper, it is intended to share a synthesis of the elaboration, execution and results of the “Virtual Workshop of Creative Sustainability”, which was developed monthly through the social network Instagram, during eight (08) months of the year 2021. The workshop happened virtually due to the Covid-19 seclusion during the critical period of the pandemic. Aiming to expose and teach, in a simple, practical and objective way, the possible paths for transforming alternative materials, which would be discarded, into new possibilities for creation of decorative objects, furniture and other pieces with multiple purposes, created by the participants themselves, by encouragement of the use of creativity. The application methodology was through a challenging format and aimed to explore the potential of creations through a simple, intuitive and unique question, as a starting point to use the imagination in the most abstract way, questioning what could be done with the respective unused materials. At the end, it was handed to the participants files in multiple formats, in order to enable the inclusion of those who do not use civil construction creation software, to demonstrate the possibility of their projects becoming real. As the expected results of the experiment revealed, after the workshop, a rich perception of the possibility of the usage of creativity as a way to recycle materials, positively impacting the pillars of sustainability. The results contribute positively to the field of architecture and urbanism, with an innovative teaching typology and community of practice for students, families and community as a whole.